A Strategy to Balance Supply and Demand Fluctuation for RES-Based Microgrids in Isolated Area - Wijaya, Fransisco Danang; Syafrudi, Syafrudi; Sarjiya, Sarjiya (2022)
RES-based microgrids are often threatened by critical conditions due to variations in solar radiation in PV plants or wind intensity in wind turbines. This study provides a strategic framework to balance the supply and demand fluctuation for RES-based microgrids in an isolated area. By proposing the NILM, the load can be separately monitored for load shedding later when a critical condition occurs. NILM based on Data-Flow Programming (BDT) offers an appropriate NILM method to be applied to isolated areas. The infrastructure needed to implement the proposed method is related to building a monitoring station equipped with a set of computers and sensors so that the NILM algorithm can proceed. The load shedding and load priority algorithm are also presented in this study to achieve customer satisfaction. The method was developed by considering the limitations of infrastructure in communication, transportation, and other technologies in isolated areas. Therefore, it is necessary to have good cooperation between grid operators and consumers so that the proposed method can work properly.